Farklı lazerlerin ortodontik aparey altındaki antibakteriyel etkilerinin değerlendirilmesi / Evaluation of antibacterial effects of different lasers under orthodontic appliances - Ünal Kundakçıoğlu, Gülşah (Bezmialem Vakıf University, 2017)
Orthodontic treatment plan may include upper jaw expansion which is often made with appliances containing acrylic. Since the appliances are fixed with bonding procedure, the patients can not remove it and clean the underneath area. This lead to the formation of an anaerobic environment. The aim of our study, is to evaluate the antibacterial / bactericidal effects of the laser technology which may minimize the harm that periodontopathogen and cariogenic bacteria in the anaerobic environment may cause. Porphyromonas gingivalis ATCC33277 and Streptococcus mutans ATCC25175 biofilms were formed on anaerobic conditions on polymethylmethacrylate discs. In order to determine the effect of different wave length lasers on decreasing the number of bacteria, Nd: YAG (1064nm), diode (810 nm) and diode (445 nm) were applied in two different powers(1,5W; 2W) and six study groups were formed. Additionally one control group without laser application was created. Polymethylmethacrylate discs with biofilm were placed in containers providing anaerobic media, and the caps of the containers were replaced with polymethylmethacrylate material. Laser application was made through the modified cap surface. Mitis Salivarius Bacitracin for S. mutans and 0.1 ml of Brucella blood (Vit K + hemin) agar for P. gingivalis were used as proliferation media and the media were incubated in anaerobic medium at 37 ° C for 72 hours. The forming colonies were counted in cfu/ ml. Additionally, Scanning Elektron Microscope (SEM) images of one disc from each study group and the control group was recorded to visualize the bacterial biofilm. In conclusion, our study showed that Nd: YAG (1064 nm), diode (810 nm) and diode (445 nm) lasers have antibacterial / bactericidal effects on S. mutans and P. gingivalis biofilms with cited parameters. It has been determined that the diode laser with the wavelength of 810 nm applied in 2 W 30 sec CW mode has the highest effect on both bacteria.

{{abstract}}
Thesis (Doktoral)--Bezmialem Vakıf University, Orthodontics Department, Istanbul, 2017
Keywords: Diş Hekimliği; Alveolar kenar artırılması; Araç-gereç ve donanımlar; Gingival hastalıklar; Lazer tedavisi; Mikroskopi-elektron taramalı; Ortodonti; Ortodontik braketler; Streptococcus mutans; Maksilla